Parenteral Lipid Emulsions Peroxidation Generated By Ambient Light: Neontal Intensive Care Unit - Maternal Perintal National Institute 2009 - admin, admin (2018)
Objective. Determine the ambient light generated by peroxidation of parenteral lipid emulsions administered to newborns in the neonatal intensive care unit of INMP in 2009. Materials and methods. A quasi-experimental, prospective, longitudinal. We studied 60 to 20% fat emulsions which were divided into 2 groups: Group 1: Parenteral lipid emulsions 20%, exposed to ambient light for a period of 24 hours under conditions of controlled temperature and humidity, which were administered to newborn born infusion bags and transparent lines and group 2: parenteral lipid emulsions 20%, exposed to ambient light for a period of 24 hours under conditions of controlled temperature and humidity, which were fed to infants in bags and protected lines photosensitive infusion. Lipid peroxidation was determined by the dosage of malondialdeico (DMA) through uptake by thiobarbituric acid (TBA) and later reading in a spectrophotometer. Intergroup comparison was performed using descriptive and inferential statistics with a significance level of less than 0,05. Results. There was a significant increase of MDA (almost 3 times higher) when the lipid emulsion was infused exposed to ambient light (unprotected) for a period of 24 hours, compared with the lipid emulsion infused with protection during the same period. Conclusions. The 20% lipid emulsions used in parenteral nutrition of infants, lipid peroxidation suffers if administered without being protected from light ambiental.La protection of such emulsions, can bring benefits to the newborn.